2017
DOI: 10.1155/2017/7831251
|View full text |Cite
|
Sign up to set email alerts
|

Effects of LncRNA BC168687 siRNA on Diabetic Neuropathic Pain Mediated by P2X7 Receptor on SGCs in DRG of Rats

Abstract: Diabetic neuropathic pain (DNP), one of the early symptoms of diabetic neuropathy, relates to metabolic disorders induced by high blood glucose, neurotrophic vascular ischemia and hypoxia, and autoimmune factors. This study was aimed at exploring the effects of long noncoding RNA (lncRNA) BC168687 siRNA on DNP mediated by P2X7 receptor on SGCs in DRG of rats. The mechanical withdrawal threshold (MWT) and thermal withdrawal latency (TWL) of rats, the expression levels of P2X7 mRNA and protein in the DRG, and ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 51 publications
0
43
0
Order By: Relevance
“…DRG neurons produce primary sensory action potentials upon peripheral stimuli and transmit the action potential signal to the spinal cord. The P2X7 receptor in DRG modulates afferent nerve activation and is involved in both neuropathic (Xie et al 2017;Wu et al 2017a) and inflammatory pain conditions (Liu et al 2017). Our recent study indicates that activation of P2X7R in microglial cells of spinal cord contributes to the inflammatory pain induced by BmK I (Zhou et al 2019).…”
Section: Discussionmentioning
confidence: 92%
“…DRG neurons produce primary sensory action potentials upon peripheral stimuli and transmit the action potential signal to the spinal cord. The P2X7 receptor in DRG modulates afferent nerve activation and is involved in both neuropathic (Xie et al 2017;Wu et al 2017a) and inflammatory pain conditions (Liu et al 2017). Our recent study indicates that activation of P2X7R in microglial cells of spinal cord contributes to the inflammatory pain induced by BmK I (Zhou et al 2019).…”
Section: Discussionmentioning
confidence: 92%
“…Additionally, a recent study showed that uc.48+ participate in pain transmission in trigeminal neuralgia, the most common NP in the facial area, via upregulating expression of P2X7 receptor and furthermore enhance the phosphorylation of ERK1/2 [52]. Similarly, BC168687 siRNA inhibited the expression of P2X7 receptors and influenced the pathological process of DNP [53,54]. In another study, MRAK009713 directly interacted with the P2X3 protein expressed in the CCI rat model and potentiated P2X3 receptor function [55].…”
Section: Lncrnas Mediate P2x Receptorsmentioning
confidence: 93%
“…3). For instance, studies have shown that the MAPK and NF-κB signaling pathways regulated by lncRNAs may be responsible for the majority of inflammatory mediator-signaling actions within nociceptive neurons [54,60,79,80]. The ERK pathway, as a branch of the MAPK signaling pathway, is another main pathway that indicates a relationship between lncRNAs and NP [61,80].…”
Section: Lncrnas Involved In Signaling Pathways Of Npmentioning
confidence: 99%
“…lncRNAs down-regulate voltage-gated channels and one of the first lncRNAs found to be implicated in pain is the endogenous voltage-gated potassium channel (K v ) Kcna2-antisense-RNA (NAT), which upon nerve injury is transcriptionally induced by myeloid zinc finger protein 1 (MZF1) and specifically targets and down-regulates Kcna2, resulting in reduced potassium currents and increased DRG excitability [202]. Other up-regulated lncRNAs, such as BC168687 [192,193], MRAK009713 [194], NONRATT021972 [177,178,195] and uc.48+ [178,179], contribute to mechanical hypersensitivity via cell-type specific interactions and induction of different purinergic receptors known for their pain modulating properties. For example, NONRATT021972 and uc.48+ up-regulate the ionotropic purinoreceptor P2X 3 in small-medium DRG neurons but P2X 7 in satellite glia cells [177][178][179]195].…”
Section: Lncrnas Deregulated In the Dorsal Root And Trigeminal Gangliamentioning
confidence: 99%